2023
DOI: 10.3389/ti.2023.10742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of T3 Administration on Ex Vivo Rat Hearts Subjected to Normothermic Perfusion: Therapeutic Implications in Donor Heart Preservation and Repair

Abstract: The present study investigated the effects of triiodothyronine (T3) administration in ex vivo model of rat heart normothermic perfusion. T3 is cardioprotective and has the potential to repair the injured myocardium. Isolated hearts were subjected to normothermic perfusion (NP) with Krebs-Henseleit for 4 h with vehicle (NP) or 60 nM T3 in the perfusate (NP + T3). Left ventricular end diastolic pressure (LVEDP), left ventricular developed pressure (LVDP), perfusion pressure (PP) and percentage of change of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…T3 seems to affect microvasculature, debilitating tissue hypoxia microvascular dysfunction following normothermic perfusion. We found that T3 administration after 4 h of normothermic perfusion resulted in a significantly lower coronary perfusion pressure as compared to untreated hearts, indicating the reduced resistance of coronary vessels [69]. Similar observations have been reported in experimental settings of microvascular dysfunction in ischemia-reperfusion injury.…”
Section: The Role Of Triiodothyronine (T3) In Machine Normothermic Pe...supporting
confidence: 89%
See 1 more Smart Citation
“…T3 seems to affect microvasculature, debilitating tissue hypoxia microvascular dysfunction following normothermic perfusion. We found that T3 administration after 4 h of normothermic perfusion resulted in a significantly lower coronary perfusion pressure as compared to untreated hearts, indicating the reduced resistance of coronary vessels [69]. Similar observations have been reported in experimental settings of microvascular dysfunction in ischemia-reperfusion injury.…”
Section: The Role Of Triiodothyronine (T3) In Machine Normothermic Pe...supporting
confidence: 89%
“…Mourouzis et al showed that the administration of T3 during normothermic perfusion with non-blood crystalloid buffer was shown to have favorable effects on cardiac function and perfusion pressure, and switched death to pro-survival kinase signaling. Especially, the improvement of coronary perfusion pressure with the addition of T3 in the perfusate indicates a favorable effect on microvascular function during ex vivo normothermic perfusion [68,69]. Experimental evidence suggests that T3 exerts its cardioprotective actions likely by suppressing pro-apoptotic signaling, such as p38 MAPK and JNKs, and increasing the activation of cardioprotective molecules like PI3 K/Akt and AMPK.…”
Section: The Role Of Triiodothyronine (T3) In Machine Normothermic Pe...mentioning
confidence: 99%